Insights into the Roles of Gut Microbes in Obesity - Sanz, Yolanda; Santacruz, Arlette; De Palma, Giada (Interdisciplinary Perspectives on Infectious Diseases, 2008)
Obesity is a major public health issue as it enhances the risk of suffering several chronic diseases of increasing prevalence. Obesity results from an imbalance between energy intake and expenditure, associated with a chronic low-grade inflammation. Gut microbes are considered to contribute to body weight regulation and related disorders by influencing metabolic and immune host functions. The gut microbiota as a whole improves the host's ability to extract and store energy from the diet leading to body weight gain, while specific commensal microbes seem to exert beneficial effects on bile salt, lipoprotein, and cholesterol metabolism. The gut microbiota and some probiotics also regulate immune functions, protecting the host form infections and chronic inflammation. In contrast, dysbiosis and endotoxaemia may be inflammatory factors responsible for developing insulin resistance and body weight gain. In the light of the link between the gut microbiota, metabolism, and immunity, the use of dietary strategies to modulate microbiota composition is likely to be effective in controlling metabolic disorders. Although so far only a few preclinical and clinical trials have demonstrated the effects of specific gut microbes and prebiotics on biological markers of these disorders, the findings indicate that advances in this field could be of value in the struggle against obesity and its associated-metabolic disorders.